A PEMANFAATAN PASIR PUTIH SEBAGAI BAHAN PEMBUATAN BETON MUTU TINGGI - Abdi Nasrullah; Dendi Nokison (Jurnal Ilmiah BERING, 2022)
This study aims to determine the content or content of mud in fine and coarse aggregates for concrete mixtures. Utilization of white sand as fine aggregate and in concrete mixtures. The test object is made in the form of a cube with 15 x 15 cm. As many as 20 specimens were made, the compressive strength of the concrete was investigated at the age of 3,7,14,21,28 days, the cement used was PCC cement. Testing / testing includes the compressive strength of concrete. The stage of mixing or stirring between cement, sand, and water. done homogeneously. The quality of the planned concrete is fc = 26 MPa. From the results of the study, the average compressive strength value of 28 days of concrete was obtained. Concrete using fine white sand aggregate obtained a compressive strength value of ; 35,555 MPa. The mud content is 3.15% for white sand and 2.17% for the Lematang river